Energy price variation estimation using an ANFIS model - Moreno, Julián; Medina, Santiago (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
This article presents the implementation of an ANFIS model to estimate price movements in the energy market in Colombia in the short term with regard to hydrological conditions in order to support the decision making process of the involved agents. The proposed model considers three input variables: an ENSO phenomenon forecast, the system's reservoir level and the hydraulic contributions of the rivers to the generation plants. The model was trained and validated with actual monthly data from 1999 until 2007. According to the results, the model captures the price tendency in an accurate way, but it must be complemented with other models that reflect the influence of other factors in the energy price formation process in this country or in others with similar features.